Direct observation of ultrafast collective motions in CO myoglobin upon ligand dissociation - Barends, Thomas R. M.; Schlichting, Ilme (Science, 2015)
Observing ultrafast myoglobin dynamics - The oxygen-storage protein myoglobin was the first to have its three-dimensional structure determined and remains a workhorse for understanding how protein structure relates to function. Barends et al. used x-ray free-electron lasers with femtosecond short pulses to directly observe motions that occur within half a picosecond of CO dissociation (see the Perspective by Neutze). Combining the experiments with simulations shows that ultrafast motions of the heme couple to subpicosecond protein motions, which in turn couple to large-scale motions. - Science, this issue p. 445, see also p. 381 - The hemoprotein myoglobin is a model system for the study of protein dynamics. We used time-resolved serial femtosecond crystallography at an x-ray free-electron laser to resolve the ultrafast structural changes in the carbonmonoxy myoglobin complex upon photolysis of the Fe-CO bond. Structural changes appear throughout the protein within 500 femtoseconds, with the C, F, and H helices moving away from the heme cofactor and the E and A helices moving toward it. These collective movements are predicted by hybrid quantum mechanics/molecular mechanics simulations. Together with the observed oscillations of residues contacting the heme, our calculations support the prediction that an immediate collective response of the protein occurs upon ligand dissociation, as a result of heme vibrational modes coupling to global modes of the protein. - Time-resolved crystallography at an x-ray laser reveals ultrafast structural changes in myoglobin upon ligand dissociation. [Also see Perspective by Neutze] - Time-resolved crystallography at an x-ray laser reveals ultrafast structural changes in myoglobin upon ligand dissociation. [Also see Perspective by Neutze]
Gesehen am 05.08.2020